Investigation of the characteristics of a semiconductor laser diode as a transceiver for fiber Bragg gratings interrogation - Oshlakov, V.S.; Aleinik, A.S.; Volkovskiy, S.A.; Smirnov, D.S. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
The paper presents the results of an experimental study of the possibility of using a narrow-band semiconductor distributed feedback laser diode used as a source and detector of optical radiation to detect the spectral response from a fiber Bragg grating. The DFB laser “LDI-1550-DFB-2.5G-20/70” from the company “Laserscom”, mass-produced on the Russian market and having standard characteristics, was chosen as the laser diode under study. To sweep the central wavelength of a semiconductor distributed feedback laser diode in the range 1549.5–1552 nm, direct pulse current modulation was used with a frequency of 100 kHz, a duty cycle of 40, and a current value of 1 A per pulse. The radiation reflected from the fiber Bragg grating corresponding to the central Bragg wavelength was recorded as a change in voltage at the anode and cathode of the laser diode due to the photoelectric effect in the laser diode. An experimental assessment of the optoelectronic parameters of a laser diode in photovoltaic and short-circuit modes was carried out: dark current, bandwidth and spectral sensitivity. The evaluation was carried out at a temperature of 25 °C. A measuring circuit has been created to detect the response from a fiber Bragg grating based on direct pulse current modulation and the photovoltaic mode of a semiconductor distributed feedback laser diode. It is shown that the photovoltaic mode of the laser diode is applicable to problems of recording optical radiation. The amplitude-frequency characteristic of a laser diode in the photovoltaic mode was experimentally obtained depending on the forward bias voltage. It is experimentally found that the –3 dB bandwidth is 300 MHz and the maximum sensitivity is 0.1 A/W in short-circuit mode, and the amplitude response is linear in the wavelength range from 1540 to 1560 nm. For the laser diode under study, the reverse branch of the current-voltage characteristic was experimentally obtained and the dark current at zero bias of the laser diode is 12.5 pA. The demonstrated method of FBG interrogation can be used for miniaturization and simplification of optical devices for fiber Bragg grating interrogation. The obtained results may be useful to specialists in fiber optic sensors, system for interrogation and processing signals from fiber optic sensors.